Accuracy of Impression Techniques for Impants. Part 2-Comparison of Splinting Techniques - Gennari Filho, Humberto [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Vedovatto, Eduardo; Assunção, Wirley Goncalves [UNESP]; Santos, Paulo Henrique dos [UNESP] (Wiley-Blackwell, 2009)
Purpose: The aim of this study was to compare splinting techniques for impression copings of osseointegrated implants with different angulations.Materials and Methods: Replicas (N = 24) of a metal matrix (control) containing two implants at 90 degrees and 65 degrees in relation to the horizontal surface were obtained by using four impression techniques: Technique 1 (T1), direct technique with square copings without union in open trays; Technique 2 (T2), square copings splinted with dental floss and autopolymerizing acrylic resin; Technique 3 (T3), square copings splinted with dental floss and autopolymerizing acrylic resin, sectioned and splinted again with autopolymerizing acrylic resin; Technique 4 (T4), square copings splinted with prefabricated acrylic resin bar. The impression material was polyether. The replicas were individually scanned to capture the images, which were assessed in a graphic computation program. The program allowed the angulation between the bases of the replicas and the reading screws to be measured. The images of the replicas were compared with the matrix image (control), and the differences in angulations from the control image were calculated. The analysis of variance and the Tukey test for comparisons (p < 0.05) were used for statistical analysis.Results: All groups showed significant differences in the implant angulations in comparison with the control group (p < 0.05). Group T1 showed the highest difference (1.019 degrees) followed by groups T2 (0.747 degrees), T3 (0.516 degrees), and T4 (0.325 degrees), which showed the lowest angular alteration compared to the control group. There were significant differences between inclined and straight implants in all the groups, except in group T4.Conclusions: Based on the results, the splinting of pick-up impression copings is indicated for osseointegrated implant impressions. The square copings splinted with a prefabricated acrylic resin bar presented the best results among the pick-up impression techniques evaluated in this study.
Keywords: Dental implants; prosthesis; impression technique